EMPIRICAL ANALYSIS OF THE PROFITABILITY AND INDEBTEDNESS IN LISTED COMPANIES – EVIDENCE FROM THE FEDERATION OF BIH - Dragan Gabrić (Economic Review)
Research on relationship between profitability and indebtedness is an interesting scientific and professional question because it is the basic criterion of performance and security in business. The aim of this paper is to examine the and determine the level of correlation between profitability and indebtedness, and to research the differences in the level of regarding company's profitability. The secondary data for the purposes of the empirical research were collected through the analysis of publicly available financial financial statement on a sample of companies listed on Sarajevo Stock Exchange in the period from 2010. to 2013. The results of the correlation analysis indicate that there is a negative correlation between profitability indicators and indebtedness within the researched companies in the observed period, which was specially indicated through the Total debt in the number of years and Interest coverage ratio. The results of testing the difference in the indicators of indebtedness regarding profitability indicate that there is a difference in the indebtedness indicators measured by the Total debt in the number of years and Interest coverage ratio, between the companies that achieved positive financial result and the companies that achieved negative financial result.